2018
DOI: 10.1021/acs.jpclett.8b03466
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Optical Picocavities below 1 nm3 Accessing Single-Atom Geometries

Abstract: Reproducible confinement of light on the nanoscale is essential for the ability to observe and control chemical reactions at the single-molecule level. Here we reliably form millions of identical nanocavities and show that the light can be further focused down to the subnanometer scale via the creation of picocavities, single-adatom protrusions with angstrom-level resolution. For the first time, we stabilize and analyze these cavities at room temperatures through high-speed surface-enhanced Raman spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
158
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(171 citation statements)
references
References 31 publications
8
158
0
5
Order By: Relevance
“…The computer then automatically moved the motorized stage to the next particle, and the process was repeated (hundreds of NPoMs in each single experiment). We note that the weak light emission from individual NPoMs of 1 k-counts/mW/s integrated or 0.5 counts/mW/s/ pixel in images means that integration times of 10 s are required to adequately discriminate the different shapes, hence integrating over any more rapidly fluctuating phenomena such as the recently described picocavities (10,48,51).…”
Section: Methodsmentioning
confidence: 99%
“…The computer then automatically moved the motorized stage to the next particle, and the process was repeated (hundreds of NPoMs in each single experiment). We note that the weak light emission from individual NPoMs of 1 k-counts/mW/s integrated or 0.5 counts/mW/s/ pixel in images means that integration times of 10 s are required to adequately discriminate the different shapes, hence integrating over any more rapidly fluctuating phenomena such as the recently described picocavities (10,48,51).…”
Section: Methodsmentioning
confidence: 99%
“…5 qualitatively shows how Å-or nanoscale-scale surface protrusions already exist at the surface and how morphological changes during the experiment time can be understood in terms of the proposed dynamic creation and annihilation of picocavities (demonstrated by ref. [47][48][49]. By looking at the TEM image of the tip apex, i.e., the last particle of the tip, we can see that the surface contains defects that are partially disorganized in comparison with a crystal facet.…”
Section: Surface Morphological Characteristics Of the Ters Tipsmentioning
confidence: 99%
“…Their main hypothesis is that the so-called persistent lines, in other words, bands that appear in all spectra, appear because of the single dipole resonance of the particle, whereas blinking lines, i.e., strong bands that appeared after laser irradiation originate from picocavity formation that further confines the field, induces a drastic change in selection rules and leads to the appearance of infrared active modes in the Raman spectra 47 . The original concept was recently extended to silver 48 and gold particles 49 , where it has been shown that plasmonic picocavities are stable for a few seconds under ambient conditions. As our experiment is conceptually similar to the method of Benz et al 47 , we will discuss the results in view of our access to the plasmon parameters and the temperature.…”
Section: Surface Morphological Characteristics Of the Ters Tipsmentioning
confidence: 99%
“…1-7 Such systems, generally referred to as nanogap plasmonic structures, can squeeze light down to deep sub-wavelength volumes, allowing for the optical radiation to probe sub-atomic interactions. [8][9][10][11][12][13][14][15][16] Most of metallic systems however, still suffer from some degree of inhomogeneity due to nanoscale surface roughness, [17][18][19] which results in deviations of the optical properties with respect to ideally smooth systems. 20,21 Recent publications have reported on the important role of surface roughness on the far-and near-field as well as nonlinear optical properties of nanoparticles.…”
mentioning
confidence: 99%